Acute effects of different warm-up protocols on sports performance in elite male collegiate handball players - Chen, C. H.; Chang, C. K.; Tseng, W. C.; Chiu, C. H.; Dai, X.; Ye, X. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to examine the effects of 3 different warm-up protocols on subsequent sports performance in elite male collegiate handball players. Fifteen handball players (19.0 ± 2.4 years) completed 3 separated randomly sequenced experimental visits. During each visit, they started with different warm-up protocols (traditional warm-up [TRAD] vs. warm-up with core stability exercises [CORE] vs. warm-up with elastic band exercises [ELAS]) and completed with a series of randomly ordered sport-specific performance testing measurements: 30-m sprint, countermovement jump, medicine ball overhead forward throw, and standing and jump handball throw tests. Both CORE and ELAS protocols induced statistically significant differences (p < 0.05) on overall sports performance (sprint time, jump height, medicine ball throwing peak velocity and power, and handball throwing velocities), as compared to the TRAD. In addition, the ELAS protocol imposed small-to-medium effects (effect size range: 0.45-0.82), enhancing handball throwing velocity and medicine ball throwing performance comparing with the CORE. Sport-specific warm-up protocols that contain core stability or elastic band-based exercises likely induced subsequent performance enhancements (sprint, jump, and throw) in elite male collegiate handball players when compared with TRAD. Furthermore, including elastic band exercises in the warm-up protocol even induced superior upper-body performance enhancement (explosive power and handball throwing velocity) than other protocols. Therefore, preconditioning warm-up activities using elastic band-based exercises can be integrated into a traditional sport-specific warm-up protocol for elite collegiate handball players before competition or training.